PENGEMBANGAN SISTEM INFORMASI UNTUK MEMFASILITASI PROSES ADOPSI ANJING BERBASIS WEB - Amelinda Chendra; Kristina G. Simanjuntak; Andree E. Widjaja; Suryasari Suryasari (Jurnal Ilmiah Matrik, 2019)
Nowadays, the application of information systems can be applied in many fields, one of which is to support the process of adopting dog as a pet. The purpose of this research therefore is to develop an integrated information system that can be used to facilitate the process of adopting dogs. The developed information system which is web-based has several main functions, such as searching for dogs, managing adoption requests, monitoring dogs that have been adopted, and periodically managing user reports. The proposed system was developed using Rapid Application Development method, PHP programming language, Code Igniter frameworks, and MySQL database. Meanwhile, the system was tested using the black box testing method.